A bibliometric analysis of inquiry learning in primary education - Wulandari, Aulia; Sukarno, Sukarno; Matsuri, Matsuri (Journal of Education and Learning (EduLearn), 2025)
The selection of a learning model is very crucial before the teacher carries out learning activities. Inquiry is a learning model that has existed for a long time and is recommended for use in learning activities. This study aims to map the results of studies related to inquiry learning in elementary schools. Bibliometrics is used as a method to map previous research. Data was obtained through the Scopus website from 2018–2022, and 143 datasets were obtained. Data analysis uses VosViewer software, which maps the data. The results revealed that the two authors have the highest total strength among the other documents. Meanwhile, based on sources, the International Journal of Science Education is the source with the highest link strength, and the Journal of Instruction is the source that is most widely cited. The Netherlands is the country with the highest number of connections, with 19 documents. Based on the author's curriculum keywords, reading dialogue, science education, and primary education are the most used keywords in 2021. Meanwhile, "narrative inquiry," "science teaching," and "professional teaching" are the least used keywords. The conclusion of this research is that inquiry is still one of the choices used in learning activities.